2010
DOI: 10.1038/nchem.699
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-selective assembly of tweezer molecules on linear templates enables frameshift-reading of sequence information

Abstract: Information storage and processing is carried out at the level of individual macromolecules in biological systems, but there is no reason, in principle, why synthetic copolymers should not be used for the same purpose. Previous work has suggested that monomer sequence information in chain-folding synthetic copolyimides can be recognized by tweezer-type molecules binding to adjacent triplet sequences, and we show here that different tweezer molecules can show different sequence selectivities. This work, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 42 publications
3
56
0
1
Order By: Relevance
“…Indeed, molecular information can be potentially stored in any synthetic polymer chain composed of two or more comonomers. Yet, robust pathways for writing[10b] and reading information on synthetic polymer chains need to be developed. In this context, the aim of the present work is to investigate facile chemical protocols allowing molecular encryption.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, molecular information can be potentially stored in any synthetic polymer chain composed of two or more comonomers. Yet, robust pathways for writing[10b] and reading information on synthetic polymer chains need to be developed. In this context, the aim of the present work is to investigate facile chemical protocols allowing molecular encryption.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was their unexpected thermal and rheological properties that attracted our attention most, which revealed strongly end‐group‐dependent behavior for both: the shorter oligomers with high end‐group density exhibited remarkably high complex viscosity and T g values compared to their longer analogues. It is postulated that this behavior is driven by a supramolecular self‐assembly process between the bis(aminoester)tosylate catechol‐bearing end‐groups, which may include catechol self‐complexation induced by hydrogen‐bonding between hydroxyl groups of neighboring catechol moieties, electrostatic interactions from the tosylate salt components, and perhaps their synergistic combination (as, e.g., in the case of complexation of pyrene‐armed molecular tweezers with electron‐deficient oligoimides, where complementary π–π stacking between π‐rich tweezer arms and π‐poor imide guest was shown to be complemented by additional hydrogen‐bonding).…”
Section: Discussionmentioning
confidence: 99%
“…[1a-d] This Minireview highlights the basic features of reported molecular tweezers, [1e] based on the nature and flexibility of the S group. Indeed, the nature of the spacer plays a critical role in the recognition process, as recently illustrated by Zhu et al with tweezers including the same IS linked by various S, and yet capable of distinguishing specific imide sites along a polymer chain based on the nature of the spacer S. [2] Three types of spacers will be discussed herein, namely flexible, rigid and switchable (Scheme 2), although borderline examples share features from each category.…”
Section: Introductionmentioning
confidence: 98%